2014
DOI: 10.1002/bdra.23266
|View full text |Cite
|
Sign up to set email alerts
|

Limb‐body wall defect: Experience of a reference service of fetal medicine from Southern Brazil

Abstract: The results disclosed that complementary exams, such as MRI and echocardiography, are important to better define the observed defects. Some of them, such as congenital heart defects, may be more common than previously reported. This definition is essential for the proper management of the pregnancy and genetic counseling of the family. The birth of these children must be planned with caution and for the prognosis a long survival possibility, despite unlikely and rare, must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…The most common sonographic finding in our cohort was a ventral wall defect of variable severity. Open neural tube defects were observed in one‐third of the study group, more than reported by other authors . The defect was usually large and associated with scoliosis or partial agenesis of the vertebrae.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The most common sonographic finding in our cohort was a ventral wall defect of variable severity. Open neural tube defects were observed in one‐third of the study group, more than reported by other authors . The defect was usually large and associated with scoliosis or partial agenesis of the vertebrae.…”
Section: Discussionmentioning
confidence: 65%
“…Because the incidence of LBWC/BSA is extremely rare, prenatal descriptions consist mostly of case reports and small series . We report the largest cohort of fetuses with body wall malformations reported up to date in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that LBWC is almost universally lethal, especially when a ventral wall defect is present, the described case would not be considered LBWC by some experienced clinicians (Gazolla et al. ). This patient has elements of both LBWC and ABS, which is consistent with the overlap between these two syndromes; however, the medical literature has not determined whether these two conditions are separate nor has the causation of these two conditions been found.…”
Section: Discussionmentioning
confidence: 98%
“…Amniotic bands are formed from strings of ruptured amnion and are believed by some to entangle and constrict body parts causing amputation‐like or constriction disruptions; however, ABS disruptions have been found in the absence of amniotic bands and not considered for the diagnosis of LBWC (Gazolla et al. ; Hartwig et al. ; Hunter et al.…”
Section: Introductionmentioning
confidence: 99%